Experimental study of accidental leakage behaviour of liquid CO2 under shipping conditions - Al Baroudi, Hisham; Patchigolla, Kumar; Thanganadar, Dhinesh; Jonnalagadda, Kranthi (Elsevier, 2021)
CO2 shipping is a viable transport alternative when pipelines are impractical. Lack of experience in large-scale CO2 shipping projects implies uncertainty in selecting optimal cargo conditions and operational safety procedures. The risk of uncontrolled release of CO2 arises in case of mechanical failure of storage or cargo vessels, and a thorough understanding of the discharge phenomena, including the propensity for solid formation, is necessary to develop safety protocols. A refrigerated experimental setup is established in this study to investigate the release phenomena of liquid CO2 under shipping conditions. The rig features a dome-ended cylindrical pressure vessel, a discharge pipe section and a liquid nitrogen refrigeration system that enables conditioning near the triple point – at ∼0.7 MPa, 223 K - and higher liquid pressures (∼2.6 MPa, 263 K). Pressure, temperature and mass monitoring were considered to enable an extensive observation of the leakage behaviour under typical operation scenarios. Three different sets of experiments were considered to inform the designer in the selection of optimal process conditions, with low-pressure (0.7 – 0.94 MPa, 223–228 K), medium-pressure (1.34–1.67 MPa, 234–245 K) and high-pressure tests (1.83–2.65 MPa, 249–259 K) demonstrating distinct behaviours relative to phase transitions, leakage duration and solidification of inventory.
Keywords: Leakage; Operational safety; CO2 shipping; CO2 transport; CCUS; GHG